Effects of dietary Lactobacillus sp. supplementation on growth performance and nutrient retention of mahseer (Tor tambroides) - Suwarsito Suwarsito; Muhammad Azharul Rijal; Hamsah Hamsah (Acta Aquatica: Aquatic Sciences Journal, 2026)
Mahseer (Tor tambroides) is an endemic freshwater fish species with high ecological and economic value; however, its aquaculture development is constrained by slow growth performance. Dietary probiotic supplementation has been proposed as a nutritional strategy to improve growth and feed utilization. This study aimed to evaluate the effects of Lactobacillus sp. probiotic supplementation in the diet on the growth performance and nutrient retention of mahseer juveniles. The experiment was conducted for 60 days using a completely randomized design with six dietary treatments consisting of different probiotic doses (0, 15, 30, 45, 60, and 75 mg kg⁻¹ feed), each with three replicates. Relative growth, feed efficiency, protein retention, and lipid retention were measured as response variables. Research data were analyzed using one-way analysis of variance (ANOVA) followed by Duncan’s multiple range test at a 5% significance level. The results showed that dietary Lactobacillus supplementation significantly affected all measured parameters (P<0.05). Fish fed the diet supplemented with 15 mg kg⁻¹ probiotic exhibited the highest relative growth, feed efficiency, and protein retention. In contrast, higher probiotic doses did not further improve growth performance and were associated with decreased feed efficiency. Lipid retention was highest in the control group and significantly lower in probiotic supplemented treatments. These findings indicate that Lactobacillus sp. supplementation at 15 mg kg⁻¹ feed is the optimal dose for improving growth performance while reducing lipid deposition. Keywords: Growth Performance; Lactobacillus sp.; Nutrient Retention; Probiotic; Tor tambroides